2020
DOI: 10.1002/ijch.202000045
|View full text |Cite
|
Sign up to set email alerts
|

Eccentricities in Spectroscopy and Reactivity of Non‐Heme Metal Intermediates Contained in Bispidine Scaffolds

Abstract: Ligand framework in a metal complex has a pivotal role to play in orchestrating the spectroscopic and reactivity parameters. High-valent non-heme metal intermediates are known to be crucial species in the catalytic cycles of several metalloenzymes. Among the plethora of a variety of ligand frameworks employed in bioinorganic chemistry, the bispidine molecular scaffold is unique and privileged. In this review, we intend to discuss the overwhelming effects of the bispidine ligand scaffold in tuning the spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 155 publications
(320 reference statements)
0
10
0
Order By: Relevance
“…[13][14][15][16] Bispidine-iron(IV)-oxido complexes have been studied extensively. [17][18][19][20][21][22][23][24][25][26] An interesting feature is the rigidity of the bispidine scaffold that is too large for Fe IV = O and therefore enforces high redox potentials of the ferryl species. [27] A range of easily accessible ligands with differing denticity and donor sets allows to fine-tune the reactivities of the bispidine-ferryl oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Bispidine-iron(IV)-oxido complexes have been studied extensively. [17][18][19][20][21][22][23][24][25][26] An interesting feature is the rigidity of the bispidine scaffold that is too large for Fe IV = O and therefore enforces high redox potentials of the ferryl species. [27] A range of easily accessible ligands with differing denticity and donor sets allows to fine-tune the reactivities of the bispidine-ferryl oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…In biomimetic systems, a number of mononuclear non-heme iron­(III)–peroxo complexes have been synthesized and characterized spectroscopically and structurally; a notable example is an X-ray crystal structure of an iron­(III)–peroxo complex bearing a macrocyclic 14-TMC ligand, [Fe­(III)­(O 2 )­(14-TMC)] + . In many of the iron­(III)–peroxo complexes, the ν Fe–O and ν O–O stretches have been observed at ∼490 and ∼820 cm –1 , respectively, in resonance Raman (rRaman) experiments. ,,,, In reactivity studies, non-heme iron­(III)–peroxo complexes have shown nucleophilic reactivities, such as in aldehyde deformylation reactions, , as reported in heme models .…”
mentioning
confidence: 99%
“…In biomimetic systems, a number of mononuclear non-heme iron­(III)–peroxo complexes have been synthesized and characterized spectroscopically and structurally; a notable example is an X-ray crystal structure of an iron­(III)–peroxo complex bearing a macrocyclic 14-TMC ligand, [Fe­(III)­(O 2 )­(14-TMC)] + . In many of the iron­(III)–peroxo complexes, the ν Fe–O and ν O–O stretches have been observed at ∼490 and ∼820 cm –1 , respectively, in resonance Raman (rRaman) experiments. ,,,, In reactivity studies, non-heme iron­(III)–peroxo complexes have shown nucleophilic reactivities, such as in aldehyde deformylation reactions, , as reported in heme models . Herein we report for the first time the synthesis, characterization, and reactivity studies of a mononuclear non-heme iron­(III)–peroxo complex bearing a macrocyclic 13-TMC ligand, [Fe­(III)­(O 2 )­(13-TMC)] + ( 1 ), with an unusual high O–O stretching mode and unprecedented electrophilic reactivity in oxidation reactions (see Scheme ).…”
mentioning
confidence: 99%
See 2 more Smart Citations